The Effect of Generation Z Participation and Financial Technology Innovation on Community Welfare and Sustainable Development in MSMEs in Indonesia - Dama, Desi Putri; Suroso, Adi; Nurhasanah, Dila Padila (West Science Social and Humanities Studies, 2024)
This study investigates the effect of Generation Z participation and Financial Technology (FinTech) innovation on community welfare and sustainable development within Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. A quantitative research approach was employed, utilizing a cross-sectional survey design to collect primary data from MSME owners, employees, and stakeholders. Structural Equation Modeling with Partial Least Squares (SEM-PLS) was used to analyze the data and test the hypothesized relationships. The findings reveal significant positive relationships between both Generation Z participation and Financial Technology Innovation with Community Welfare and Sustainable Development. The results underscore the importance of harnessing youth entrepreneurship and technological innovations to drive socio-economic development and promote sustainable growth within the MSME sector. These findings have significant implications for policymakers, entrepreneurs, and stakeholders striving to foster inclusive and sustainable development in Indonesia.